Sanitary measures considerably improve the management of resistant Norway rats on livestock farms. Issue 4 (23rd January 2022) - Esther, Alexandra; Hansen, Sabine C; Klemann, Nicole; Gabriel, Doreen
Abstract: BACKGROUND: Norway rats ( Rattus norvegicus ) need to be controlled to prevent transmission of pathogens and damages to stored products and material, leading to considerable economic risks and losses. Given increasing resistance in Norway rats, the most persistent, bio‐accumulative and toxic anticoagulant rodenticides are widely used for management, which presents hazards to the environment especially for non‐target species. We investigated how sanitary measures improved management of Norway rats on 12 paired livestock farms in a region of Germany with a high population of resistant rats for reducing application of rodenticides. We recorded food intake, and tracked activity and resistance frequency during the pre‐treatment, treatment and post‐treatment periods. RESULTS: In the post‐treatment period, farms using sanitary measures had a higher control success with > 13% more bait boxes without feeding than farms not using sanitary measures. In addition, the reoccurrence of rats was delayed by 85 days. With increasing accessibility to buildings and more precise positioning of the boxes, control success improved, especially when rats could not spread from water‐bearing ditches through the sewer system, and when rat‐hunting animals were present. Resistant animals were more common indoors than outdoors, and there were more resistant rats recorded before and during treatment than in the post‐treatment period. CONCLUSION: The control success was substantially higher and reoccurrence was delayed using sanitary measures on farms. Sanitary measures can reduce resistance indirectly due to delayed re‐colonization and establishment of resistant populations inside buildings. Hence, sanitary measures help to reduce economic losses, rodenticides required for rat management and environmental risk especially in the resistance area. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Sanitary measures considerably improve the success of resistant Norway rat control and prolong the time until reoccurrence and thereby mitigate infection risk, rodenticide applications and environmental risk.